ENDOGAMOUS MARRIAGE OF WEST LAMPUNG SAIBATIN COMMUNITY FROM THE PERSPECTIVE OF ISLAMIC LAW - Firlina, Amria; Zuhraini, Zuhraini; firdawati, Linda (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2023)
Endogamous marriage is a union between tribes, ethnicities, and families in the same environment. Endogamous marriage in the family environment is a marriage between cousins and descendants who are the same or still have a family relationship between the two. Marriage or nayuh in the Saibatin community is carried out by people of the same tribe, one faith, and even some with close relatives. The meaning of close is marriage between third cousins and so on. With the development of the current era, the marriage system among clans or tribes has faded after a shift in social values. This study aims to analyze endogamous marriages in the Saibatin tribe according to the perspective of Islamic law. This research is field research with a descriptive-qualitative approach. The research subject comprises a married couple who have entered an endogamous marriage. The research location is in three villages from several sub-districts in West Lampung Regency. The results of the researcher's survey of respondents and correspondents show that endogamous marriages did not conflict with Islamic law. According to maqasid shari'ah, it is judged as permissible to be carried out as the law is daruriyat because it is to maintain religion, soul, mind, offspring, and property. According to urf, it is judged as shahih urf because it does not conflict with Islamic law and is based on taghayurul ahkam wal amkinah. Endogamous marriages are rare due to shifting social values in local customary law; as for the marriage law, it is mubah.